2019
DOI: 10.1108/ijmpb-03-2018-0052
|View full text |Cite
|
Sign up to set email alerts
|

Projectification of a global organization – case study of the Roman Catholic Church

Abstract: Purpose The purpose of this paper is to understand projectification processes of the global organization, based on the example of the Catholic Church’s activities. The Catholic Church is the oldest and the largest international organisation to be assessed also from the longue durée perspective. The Church as both a large and supranational organisation and a religious community has carried out a lot of social tasks. A part of its activity relating to the Church’s basic mission is carried out in these days in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…According to this concept, projectification may be seen as an ongoing activity or a result of this activity. In other words, "it is a change and leads to it" ( Jałocha et al, 2019). Here, the process refers to the changes that occurred in institutions to fit their legal and organisational shape to EU expectations.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this concept, projectification may be seen as an ongoing activity or a result of this activity. In other words, "it is a change and leads to it" ( Jałocha et al, 2019). Here, the process refers to the changes that occurred in institutions to fit their legal and organisational shape to EU expectations.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Moreover, these changes may occur gradually and thus become observable only in a long-term perspective. At the mega level, the phenomena of the projectification of entire societies ( Jensen et al, 2016;Lundin et al, 2015), countries and regions (Fred, 2018), or supranational organisations (Büttner and Leopold, 2016;Godenhjelm et al, 2015;Jałocha et al, 2019) are observed. These studies emphasise that the process of projectification has largely exceeded its original, organisational understanding and acquired a wider social dimension.…”
Section: Ijmpb 123mentioning
confidence: 99%
“…Projectification is mainly described as the use of project management tools and structures, either in work or in daily life tasks, entailing the adaptation and adoption of project models, processes, language, rituals and symbols (Bredin and Soderlund, 2006;Cicmil and Gaggiotti, 2018;Cwikla and Jalocha, 2015;Fred, 2020;Jałocha et al, 2019;Jensen et al, 2018;Maylor and Turkulainen, 2019;M€ uller et al, 2017;Munck af Rosensch€ old, 2019;Schoper et al, 2018).…”
Section: The Concept Of Projectificationmentioning
confidence: 99%
“…Projectification is also discussed according to its goals: organization of work (Ingason et al, 2019;Maylor and Turkulainen, 2019;Munck af Rosensch€ old, 2019;Schoper et al, 2018); flexibility (Cerne and Jansson, 2019); renewal (Jałocha et al, 2019), optimization and efficiency (Lundin, 2016;Dollinger, 2020); new venture creation (Li et al, 2020); goal fulfillment in team work (Auschra et al, 2019); competitive advantage enhancement (Maylor et al, 2006;Munck af Rosensch€ old and Wolf, 2017); and problem-solving improvement (Jałocha, 2019;Fred, 2020).…”
Section: Bibliographic Review and Analysismentioning
confidence: 99%
“…A more recent research cluster is studies of projectification of/in transnational and global organisations (see, e.g. B€ uttner and Leopold, 2016;Godenhjelm et al, 2015;Jałocha et al, 2019).…”
Section: Four Images Of Projectification Researchmentioning
confidence: 99%